Cognitive decline and quality of life in incident Parkinson's disease: The role of attention. (June 2016) - Lawson, Rachael A.; Yarnall, Alison J.; Duncan, Gordon W.; Breen, David P.; Khoo, Tien K.; Williams-Gray, Caroline H.; Barker, Roger A.; Collerton, Daniel; Taylor, John-Paul; Burn, David J.; ,
Abstract: Introduction: Parkinson's disease dementia (PDD) is associated with poorer quality of life (QoL). Prior to the onset of PDD, many patients experience progressive cognitive impairment. There is a paucity of longitudinal studies investigating the effects of cognitive decline on QoL. This study aimed to determine the longitudinal impact of cognitive change on QoL in an incident PD cohort. Methods: Recently diagnosed patients with PD (n = 212) completed a schedule of neuropsychological assessments and QoL measures; these were repeated after 18 (n = 190) and 36 months (n = 158). Mild cognitive impairment (PD-MCI) was classified with reference to the Movement Disorder Society criteria. Principal component analysis was used to reduce 10 neuropsychological tests to three cognitive factors: attention, memory/executive function, and global cognition. Results: Baseline PD-MCI was a significant contributor to QoL (β = 0.2, p < 0.01). For those subjects (9%) who developed dementia, cognitive function had a much greater impact on QoL (β = 10.3, p < 0.05). Multivariate modelling showed attentional deficits had the strongest predictive power (β = −2.3, p < 0.01); brief global tests only modestly predicted decline in QoL (β = −0.4, p < 0.01). Conclusions: PD-MCI was associated with poorer QoL over three years follow up. Cognitive impairment had a greater impact on QoL in individuals who developed dementia over follow-up. Impaired attention was a significant determinant of QoL in PD. Interventions which improve concentration and attention in those with PD could potentially improve QoL. Highlights: Rate of QoL decline was three times faster in PD-MCI subjects compared those with normal cognition. Cognitive decline predicted worsening of QoL over 36 months. Decline in attention was the strongest cognitive predictor of declining QoL.